After the cosmopolitan? : multicultural cities and the future of racism - Keith, Michael, 1960- (Routledge, 2005)
In After the Cosmopolitan Michael Keith argues that both racial divisions and intercultural dialogue can only be understood in the context of the urban cities that gave them birth.